The Position of the Indonesian National Sports Committee (INSC) and the Indonesian Olympic Committee (IOC) in Indonesia - Gunawan Widjaja; Rizka Anindya Manjayani; Rianti Nurul Oktavia; Nur Ulfa Maulida; Elisabeth Purnama Massang; Rafa Zahirah Husein; Farrel Abiyu Ramadhana (IHSA Institute, 2022)
World institutions that regulate sports are under the authority of the International Olympic Committee (IOC). Currently, two institutions in Indonesia, namely the in: Regional Sports Committee (RSC) and the Indonesian Olympic Committee (IOC). The Indonesian National Sports Committee (INSC) is the only organization authorized and responsible for managing, fostering, developing & coordinating the entire implementation of sports activities for each member's achievements in Indonesia. RSCis an independent and non-governmental body, meaning that sports activities return to the community. Judging from the historical aspect of the birth of Presidential Decree No. 72 of 2001, RSC was positioned as a single public legal entity that carried out coaching and development of sports and achievements. This study aimed to explain the existence, legality, and authority of RSC and IOC. This research is normative legal research with qualitative analysis using secondary data. The results of the research and analysis show that the two institutions legally go hand in hand and do not overlap.